Deeper insight into the effect of salinity on the relationship of enzymatic activity, microbial community and key metabolic pathway during the anaerobic digestion of high strength organic wastewater. (November 2022) - Yin, Yijang; Zhang, Zengshuai; Yang, Kunlun; Gu, Peng; Liu, Shiguang; Jia, Yifan; Zhang, Zhaochang; Wang, Tao; Yin, Jianqi; Miao, Hengfeng
Graphical abstract: Highlights: Butyric acid was accumulated in high salinity. High salinity reduced enzyme activity and functional gene abundance. The inhibition of β-oxidation pathway led to butyric acid accumulation. High salinity inhibited acetoclastic and methylotrophic methanogenesis pathway. Abstract: The threshold salt concentration to inhibit the anaerobic digestion (AD) has been intensively investigated, but its insight mechanism is not fully revealed. Therefore, this study systematically investigated the effect of salinity on acidogenesis and methanogenesis and its mechanism. Results showed that low salinity level (i.e. 0.6%) had stimulatory effect on volatile fatty acids (VFA) and methane production, while significant inhibition was observed with further increased salinity. Moreover, high salinity limited the butyric acid degradation at acidogenesis process. The decreases of enzymes (AK and PTA) activity and functional genes (ackA, pta and ACOX) expression that related to β-oxidation explained the butyric acid accumulation at high salinity levels. Microbial community analysis revealed high salinity levels significantly inhibited the proliferation of Syntrophomonas sp., which are known to be associated with butyric acid degradation. Similarly, the relative abundance of acetoclastic methanogen ( Methanothrix sp.) and methylotrophic methanogen ( Methanolinea sp.) significantly decreased at salinity condition.